Representação virtual jornalística : proposta de matriz para análise de conteúdos jornalísticos em realidade virtual - Rocha, Giovanni Guizzo da (2020)
This thesis investigates the development capability for journalistic practices and discourse by applying the technology called Virtual Reality (RHEINGOLD, 1991; CADOZ, 1997). Its inspiration and problematic also include the emergence of the concept defined as Immersive Journalism (DE LA PEÑA, 2010), also observed through ther perspectives that involve the possibilities of transposition with journalism (BIOCCA, LEVY, 1995; PRYOR, 2002, 2004) and the interactivity of digital technologies (MURRAY, 2003). By understanding that such productions are objects no longer determined by temporality but by spatiality (BIOCCA, LEVY, 1995; MANOVICH, 2001; PRYOR, 2002), we defend the thesis that these productions require interdisciplinary intersections with techniques and perspectives within the domain of game design for their development. To achieve this result, it is necessary to demonstrate that the very concept called virtual reality, mostly emerged from the journalist discourse of the 1990's, operates as an agent of imprecision for the field of studies (LANIER, 2017). Therefore, from the conception of a new method of understanding for the term, defined as Journalistic Virtual Representation (JVR), we have developed an original matrix which allows the analysis of productions directed at the practices and missions of journalism. Divided into technical and communicational aspects, we offer a group of categories that allows for the analysis as well as the comprehension of capabilities and limitations not only of the environment, but also of the events for the production of journalistic content. The analysis phase is composed by a corpus of five experiences developed between the years 2014 and 2019. Amongst the results identified, we emphasize the need of the proximity with interactivity and simulation techniques; the journalists' understanding about updates and technological qualifications operating as amplifiers of the responsibilities of the profession. Finally, contrary to the view of an experimental journalism (PAVLIK, 2019), we defend the constitution of an exploratory journalism.